THE DEVELOPMENT OF THE LITERARY PORTRAIT GENRE IN UZBEK LITERARY CRITICISM DURING THE YEARS OF INDEPENDENCE - Dilnavoz Tuymurodovna Nazarova (International Journal of Literature and Language Studies, 2026)
This article explores the development of the literary portrait genre in Uzbek literary criticism during the years of national independence. The study examines the theoretical foundations of the genre, its historical evolution, and the distinctive features of literary portraits created in the contemporary literary process. Particular attention is paid to the contributions of prominent literary scholars, including Abdugafur Rasulov and Umarali Normatov, whose works significantly enriched the genre and expanded its artistic and critical potential. The article analyzes the role of literary portraits in revealing the intellectual, creative, and spiritual dimensions of literary figures, while also identifying current trends in the development of portrait studies within Uzbek literary criticism. The findings demonstrate that literary portraits created during the independence period have attained a higher level of artistic maturity and methodological sophistication, allowing for a more comprehensive representation of writers and literary scholars.